Does Emotion-Inducing Digital Content Enhances Brand Equity and Brand Loyalty? Evidence from Indonesian MSEs - Daniel Peterson Silaban (Business Management, 2025)
Digital Content Marketing (DCM) plays an increasingly strategic role for micro and small enterprises (MSEs), particularly service-based businesses that rely on trust and strong branding. This study examines how emotional value, as a core dimension of DCM, influences brand outcomes in the context of service-based MSEs in North Sulawesi, Indonesia. Drawing on advertising value theory and the theory of consumption values, the research investigates the effects of emotional value on brand equity and brand loyalty, while also testing the mediating role of brand equity. A purposive survey was conducted with 226 consumers who had interacted with the Instagram accounts of local MSEs. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Results show that emotional value significantly enhances both brand equity and brand loyalty. Moreover, brand equity strongly predicts loyalty and partially mediates the relationship between emotional value and loyalty. These findings emphasize the importance of emotion-inducing digital content in strengthening brand superiority and consumer loyalty, while offering actionable insights for managers, business associations, and policymakers supporting MSE competitiveness in emerging markets.